Financial and Organizational Aspects of the Recovery of Hydrocarbon Resource Base in the Regional Context - Sharf, Irina Valeryevna (Economy of Regions, 2017)
The characteristics of hydrocarbon resource base qualitative and quantitative degrade are reflected in the increase of the share of small and medium-sized deposits, as well as hard-to-recover reserves. This makes the need to update the approaches to the implementation of the geological prospecting programmes. The geological exploration performance differs in oil-producing regions of the Russian Federation due to a number of various factors. The subject matter of the study is the assessment of the strength of these factors in various working, geological, infrastructure and economic conditions to determine the effectiveness of the existing economic model of the recovery of hydrocarbon resource base, as well as to develop the author's suggestions. The hypothesis of the study proposes to change the economic, as well as financial and tax mechanisms of government regulation of the geological exploration, carried out by small oil producing companies on license areas with one or several fields in order to stimulate the development of hydrocarbon resource base. The method of the study is the correlation analysis of the impact of various factors on geological exploration on mineral resource base recovery. It is carried out utilizing K. Mohn model and the statistical data of three subjects of the Russian Federation (the Republic of Tatarstan, Khanty-Mansiysk Autonomous District and Tomsk region). The results of the study can be applied in the tax and financial legislation, as well as in the management of oil and gas industry in the field of geological exploration. On the basis of the conducted analysis and international experience, the author suggests to introduce reasonable tax incentives and the mechanism of public private partnership in the realization of geological prospecting programmes with the aim to support small oil producing companies at the initial stage of the development of a field.